Juristic Analysis of Ṣukūk default: East Cameron Gas United States of America - Saheed Abdullahi Busari (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2019)
East Cameron gas was the first Sukuk investment experience in the United States of America. The diversification of the Sukuk into oil and gas exploration particularly in the USA was a ground success in Islamic space. However, the 2008 global economic recession hits the East Cameron gas resulting from the shortfall in sales of oil and gas. The East Cameron defaulted from financial obligation and consequently filed for chapter 11 bankruptcy. This study aims to critically analyse the judgement made by Robert Summerhays United States Bankruptcy Judge in the case of East Cameron partners L.P, v. Louisiana offshore holding, LLC. & Ors [2009]. The study employs juristic analytical approach to the court judgement of East Cameron Gas default ṣukūk by explicating exact terms of the court case. This study also analyses the validity of contractual rights and obligations of parties to a ṣukūk contract. The study concluded that despite the claim of East Cameron partners LP, that the underlying asset ORRI is a mere loan and not true-sale, the bankruptcy court decision seems to be compatible with Sharī’ah because the Islamic maxims like “Muslims are bound by their contractual agreement” is a sufficient evidence to the court decision to ensure protection of contractual parties to ṣukūk investment. This paper provides description and analysis on juristic compatibility of East Cameron court judgements and trend of Sukuk default in the USA. The study explains the Sharī’ah analysis of the underpinning argument in the East Cameron sukuk default court case.